Using a Modified Function Acquisition Speed Test (FAST) for Assessing Implicit Gender Stereotypes. - Cartwright, Aoife; Roche, Bryan; Gogarty, Michelle; O'Reilly, Anthony; Stewart, Ian (Psychological Record, 2016)
The recently developed Function Acquisition Speed Test (FAST) represents an effort to assess the relative strength of stimulus relations by traditional behavior-analytic means (i.e., acquisition curves). The current study was the first application of the FAST to the assessment of natural, pre-experimentally established stimulus relations. Specifically, this experiment assessed the sensitivity of the FAST to pervasive gender stereotypes of men as stereotypically 'masculine' (e.g., dominant or competitive) and women as stereotypically 'feminine' (e.g., nurturing or gentle). Thirty participants completed a FAST procedure consisting of two testing blocks. In one block, functional response classes were established between classes of stimuli assumed to be stereotype-consistent (i.e., men-masculine and women-feminine), and in the other, between classes of stimuli assumed to be stereotype-inconsistent (i.e., men-feminine and women-masculine). Differences in the rate of class acquisition across the two blocks were quantified using cumulative record-type scoring procedures plotting correct responses as a function of time. Acquisition rates were significantly faster (i.e., displayed steeper learning curves) for the stereotype-consistent relative to the stereotype-inconsistent block. Corroborating stereotypes were observed on an Implicit Association Test containing identical stimuli.